Genre-Based Approach Effectiveness in Writing Descriptive Text - Dzukhriyah, Silfa; Rini, Setia (Universitas Dian Nuswantoro, 2023)
This study aims to determine the effectiveness of using a genre-based approach as a learning method in teaching and improving students' writing skills. This study uses a quantitative method, using pre-test and post-tests as data collection techniques. The subjects of this research were the eighth graders of SMP Dharma Lestari, Salatiga. The results obtained were that the average score of students on the pre-test was 71.44, while the average score of students on the post-test was 76.04. This shows an increase in students' ability to learn to write by as much as 6.4%. Research has shown that the genre-based approach can be effective in improving students' writing skills, particularly in terms of organization, coherence, and clarity. By focusing on the features of different genres, students can learn how to use language to achieve specific goals and how to adapt their writing to different contexts and audiences. Therefore, it can be concluded that the genre-based approach is an effective method for teaching and improving students' writing skills.